Faktor-Faktor yang Mempengaruhi Pendapatan Asli Daerah di Daerah Sumatera - Apriyani, Dona; Nurdiawansyah; Khairudin; Amna, Luke Suciyati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study is to evaluate the variables that influence local income in the Sumatra region. This study uses quantitative methods and uses explanatory research methods. The population that was the subject of this study included local income earners in all provinces of Sumatra. The type of sample used is a saturation sample, meaning all sampling units are combined into one. The secondary data used in this study were obtained from official sources, such as the official DJPK website of the Ministry of Finance. Data collection techniques involve collecting data from existing sources. Regional original income is the dependent variable in this research. Meanwhile, GRDP (Gross Regional Domestic Product), inflation and population are independent variables. This study uses classic assumptions such as heteroscedasticity, normality, multicollinearity, and autocorrelation. Multiple linear regression analysis was used to collect data. Additionally, hypothesis testing was performed using t-test and determination (R2). The results of the study show that GDPR, inflation and population have a positive and significant impact on local income in the Sumatra region. Based on the analysis carried out, it can be concluded that policies supporting increased GDPR, inflation control and good population management can contribute to increasing initial local income. Therefore, the government should develop a policy strategy capable of supporting local revenue growth in the Sumatra region.